Ethnobotanical study of wild medicinal plants in Serbajadi protected forest of East Aceh District, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Navia ZI, Adnan, Harmawan T, Suwardi AB. 2022. Ethnobotanical study of wild medicinal plants in Serbajadi protected forest of East Aceh District, Indonesia. Biodiversitas 23: 4959-4970. The Serbajadi protected forest of East Aceh District has high biodiversity including medicinal plants which have been utilized by the community as traditional medicine. However, their knowledge of ethnobotanical uses of medicinal plants is threatened due to the lack of written records and the rapid socio-cultural changes as a consequence of economic development. Therefore, this study aims to study wild medicinal plants and traditional knowledge in the Serbajadi protected forest, East Aceh District, Indonesia. This study used a combination of data collection methods, namely field surveys, plant collections, and community interviews. The snowball sampling technique was used to select 320 interviewees. The results showed that local people use 88 different wild medicinal plant species from 78 genera and 46 families to treat 32 different diseases. The most common ailments to cure are fever, cough, and diarrhea. Ageratum conyzoides is the most known medicinal plant species with a relative frequency citation index of 0.97, while Acorus calamus is the most commonly used medicinal plant in the local community with a use value index of 0.99. Furthermore, locals identified leaves (75%) as the most commonly used plant part and decoction (55%) as the most common method of administering traditional medicine. The elders know more about medicinal plants than the younger generation, indicating that traditional knowledge is eroding as generations pass. In order to ensure the sustainability of medicinal plants and the preservation of traditional knowledge in the future, the initiative to preserve medicinal plants must be increased, particularly among the younger generation.